2017
DOI: 10.1371/journal.pone.0185951
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mandibular setback with or without maxillary advancement osteotomies on pharyngeal airways: An overview of systematic reviews

Abstract: BackgroundMandibular setback osteotomies potentially lead to narrowing of the pharyngeal airways, subsequently resulting in post-surgical obstructive sleep apnea (OSA).ObjectiveTo summarize current evidence from systematic reviews that has evaluated pharyngeal airway changes after mandibular setback with or without concomitant upper jaw osteotomies.MethodologyPubMed, EMBASE, Web of Science, and Cochrane Library databases were searched with no restriction of language or date. Systematic reviews studying changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 49 publications
0
16
0
2
Order By: Relevance
“…Currently, it is widely accepted that a relative reduction of the pharyngeal airway space (PAS) could be resulted from mandibular setback. Although some papers have reported patients who were diagnosed with mild OSA after MSS 1,2 , there is no evidence for postoperative OSA 35 . However, many authors have recommended simultaneous double jaw surgery consisting of maxillary advancement and mandibular setback for severe class III patients not only to reduce the amount of mandibular setback, but also to lower the risk of pharyngeal airway compromise because of the possibility of postoperative OSA 69 .…”
Section: Introductionmentioning
confidence: 99%
“…Currently, it is widely accepted that a relative reduction of the pharyngeal airway space (PAS) could be resulted from mandibular setback. Although some papers have reported patients who were diagnosed with mild OSA after MSS 1,2 , there is no evidence for postoperative OSA 35 . However, many authors have recommended simultaneous double jaw surgery consisting of maxillary advancement and mandibular setback for severe class III patients not only to reduce the amount of mandibular setback, but also to lower the risk of pharyngeal airway compromise because of the possibility of postoperative OSA 69 .…”
Section: Introductionmentioning
confidence: 99%
“…Notably, one case reported a ∆area increase of 50% at the level of the nasopharynx following MAMS (mandibular setback: −3.68 mm; maxillary advancement: +7.2 mm). It is reasonable to hypothesize that a higher degree of upper maxillary forward translation counteracts the reduction in surface area that mandibular setback may induce, as previously reported [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 52%
“…Although airway narrowing was improved after surgery, the pharyngeal airway volume remained lower compared with the preoperative airway volume. The comparative studies and meta-analysis of mandibular setback surgery have shown that maxillary advancement or maxillary posterior impaction would be able to attenuate the narrowing of the airway [2,27]. The AHI is defined as the total number of apneas and hypopneas per hour of sleep by polysomnography.…”
Section: Significant Airway Reduction After Mandibular Setback Surgerymentioning
confidence: 99%
“…Interestingly, even for an underweight patient with a normal AHI (BMI of 18.9, preoperative AHI of 0.2), the AHI was increased to 7 [4]. However, a recent review of previously published systematic reviews suggested that although the development of postsurgical OSA has been reported, there is no clear evidence that confirms a direct cause-and-effect relationship between mandibular setback surgery and OSA development [27]. For patients with severe mandibular prognathism or patients with potential for OSA development, two-jaw surgery should be strongly considered [34].…”
Section: Significant Airway Reduction After Mandibular Setback Surgerymentioning
confidence: 99%